The effect of extracts and essential oil from invasive Solidago spp. and Fallopia japonica on crop-borne fungi and wheat germination - Anžlovar, Sabina (Array, 2020)
Research background. Many plant extracts and essential oils show antibacterial and antifungal activities, with potential to replace the use of synthetic fungicides. We used invasive alien plants goldenrod (Solidago spp.) and Japanese knotweed (Fallopia japonica) as source materials to determine their antifungal activities against seed-associated fungi from wheat grain (Alternaria alternata, Alternaria infectoria, Aspergillus flavus, Epicoccum nigrum and Fusarium poae).Experimental approach. Aqueous and organic extracts (ethanol, methanol and acetone) were prepared from leaves and flowers of S. canadensis, S. gigantea and S. virgaurea, and leaves and rhizomes of F. japonica. Additionally, essential oils were distilled from Solidago flowers and leaves. The extracts and essential oils were tested as inhibitors of fungal growth in vitro. Solidago essential oils were tested also as antifungal agents for protection of wheat grain by determining its fungal infection and germination rate.Results and conclusions. The extracts showed a wide spectrum of low to moderate antifungal activities, with those of Solidago spp. generally more effective than those of F. japonica, and organic extracts more effective than aqueous extracts. The essential oils from leaves and flowers had similar antifungal activity and whole shoots can be collected for their production. This study presents the systematic study of the composition of essential oils from flowers and leaves of three widely distributed Solidago spp. in Slovenia, with the major constituents of terpenes and terpenoids α-pinene, germacrene D and bornyl acetate.Novelty and scientific contribution. The study presents the first use of Solidago spp. and Fallopia japonica extracts and essential oils against fungal strains isolated from wheat grain.